2019
DOI: 10.1111/ane.13081
|View full text |Cite
|
Sign up to set email alerts
|

MUL1 gene polymorphisms and Parkinson’s disease risk

Abstract: | INTRODUC TI ONParkinson's disease (PD) is the second most common neurodegenerative disorder worldwide characterized by dopaminergic neuron loss in the substantia nigra. 1 PD expresses as some motor symptoms (MS) like tremors, slowness, rigidity, as well as some non-motor symptoms (NMS) include dementia, depression, constipation, et al 2,3 Although drugs can help to release the pain and movement disorder, PD cannot be cured or halted at present. 4 Recently, several genome-wide association studies (GWAs) ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…There were few studies investigating the role of MUL1 in the development of dementia in PD, and one case-control study conducted in China showed that MUL1 SNP rs529974 was correlated with the development of PD [ 30 ]. MUL1 encodes mitochondrial ubiquitin ligase 1, a mitochondrial E3 protein ligase that regulates mitofusin.…”
Section: Discussionmentioning
confidence: 99%
“…There were few studies investigating the role of MUL1 in the development of dementia in PD, and one case-control study conducted in China showed that MUL1 SNP rs529974 was correlated with the development of PD [ 30 ]. MUL1 encodes mitochondrial ubiquitin ligase 1, a mitochondrial E3 protein ligase that regulates mitofusin.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of VPS35 gene in SH-SY5Y and NLT cell lines causes intracellular accumulation of a-syn (Tang et al, 2015). A separate report, in a Chinese cohort study, showed that the gene MUL1 is a risk factor for PD (Taximaimaiti and Li, 2019). Another protein, MIRO1, a Rho GTPase gets localized both in the peroxisomes and mitochondria in mammals (Castro et al, 2018;Okumoto et al, 2018;Farr e et al, 2019).…”
Section: Lrrk2mentioning
confidence: 99%
“…Overexpression of MUL1 in the fruit fly model suppresses the PD phenotype caused by loss of PINK or PARKIN 32 . Therefore, endogenous MUL1 levels in PINK/PARKIN mutants would exert a compensatory role 32,60 . This compensatory effect may be explained because both MUL1 and PARKIN are E3 ligases that ubiquitinate Mfn2 for degradation.…”
Section: Mul1 In Pathological Conditionsmentioning
confidence: 99%
“…The T allele of rs529974 located in the 3′‐untranslated regions was a risk factor for PD, whereas the C allele of rs529974 was shown to be a protective factor. Thus, mutations in MUL1 are a promising blood biomarker for the early diagnosis of PD 60 . MUL1 is also implicated in some behavioral symptoms of PD, such as sleep disturbances, which could exacerbate disease progression, and nonmotor symptoms, such as altered circadian rhythms of blood pressure and core body temperature 59 …”
Section: Mul1 In Pathological Conditionsmentioning
confidence: 99%
See 1 more Smart Citation